The Curvilinear Ethnoaesthetic in Pangalay Dancing among the Suluk in Sabah, Malaysia - Desiree A. Quintero,; Mohd Anis Md Nor, (Wacana Seni Journal of Arts Discourse, 2016)
Pangalay refers to a dancing among the Suluk people in Sabah, Malaysia performed primarily during social occasions that focuses on movement motifs of the hands and arms, moving in a slow and sustained way with a musical ensemble called kulintangan. Pangalay integrates spontaneity and imagination through the agentic process of a dancer, that is grounded in visual notions of the curvilinear, denoting kinaesthetically bound movement imbued with the aesthetic qualities of curving and curling in space of the body, specifically in the movement motifs of hands, arms and for some dancers, asymmetry of the bodyline. The curvilinear as abstraction is an aesthetic experience premised on the idea of the bending of or deviation from the straight line, as in the curve, and the twisting and turning of the line, as in the curl. This concept is embodied in both the kulintangan motifs that rise and fall, rhythmically slow or quicken, and in the movement motifs executed by the dancer that curve and curl through space. Pangalay is improvisation of movement within aesthetic conventions of the curvilinear that are culturally shaped, reflecting the ethnoaesthetic of the Suluk people.